Klasifikasi Opini Pengguna Media Sosial Twitter Terhadap JNT Di Indonesia dengan Algoritma Decision Tree - Handoko, Widiyanto Tri; Supriyanto, Edy; Purwadi, Dimas Indra; Budiarso, Zuly; Listiyono, Hersatoto (STIKOM Tunas Bangsa Pematangsiantar, 2022)
JNT Ekspress is one of the many freight forwarding companies that exist today, where JNT has very wide access so it is very easy to use for the public in shipping goods. With the current network, JNT is able to deliver goods to all provinces in Indonesia. With the large number of users, of course there will be a lot of user opinions that appear, both positive and negative opinions. In order to be able to categorize multiple opinions, a machine learning program is needed that can simplify the process of grouping the opinion. There are many algorithms that can be used to classify opinions, one of them is Decision Tree. Prior to grouping or classification, Tweet data that has been collected needs to be preprocessed first so that the tweet data can be recognized by the system. Based on this research, the Decision Tree algorithm gets an accuracy of 94.12% with a comparison ratio of training data and testing data of 90:10